TREK-1 in the heart: Potential physiological and pathophysiological roles - Bechard, Emilie; Bride, Jamie; Le Guennec, Jean-Yves; Brette, Fabien; Demion, Marie (Frontiers in Physiology, 2022)
TREK-1 channel belongs to the TREK subfamily of two-pore domains channels that are activated by stretch and polyunsaturated fatty acids and inactivated by PKA phosphorylation. The activation of this potassium channel must induce a hyperpolarization of the resting membrane potential and a shortening of the action potential duration in neurons and cardiac cells, two phenomena being beneficial for these tissues in pathological situations like ischemia-reperfusion. Surprisingly, the physiological role of TREK-1 in cardiac function has never been thoroughly investigated, very likely because of the lack of a specific inhibitor. However, possible roles have been unraveled in pathological situations such as atrial fibrillation worsened by heart failure, right ventricular outflow tract tachycardia or pulmonary arterial hypertension. The inhomogeneous distribution of TREK-1 channel within the heart reinforces the idea that this stretch-activated potassium channel might play a role in cardiac areas where the mechanical constraints are important and need a particular protection afforded by TREK-1. Consequently, the main purpose of this mini review is to discuss the possible role played by TREK -1 in physiological and pathophysiological conditions and its potential role in mechano-electrical feedback. Improving understanding of the contribution of TREK-1 in the heart may help in development of promising and challenging treatment of cardiac diseases.